2016
DOI: 10.1186/s12913-016-1425-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the current practice of self-medication consultations in Eastern Indonesian community pharmacies: a qualitative study

Abstract: BackgroundResearch has shown that the current practice of pharmacy staff when providing self-medication consultations in Indonesia is suboptimal. To improve the performance of pharmacy staff when providing self-medication consultations in community pharmacies, the factors that influence current practice need to be understood. The aim of this study is to identify the factors that influence current practice of pharmacy staff when handling self-medication consultations in Eastern Indonesian community pharmacies.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 28 publications
4
31
0
9
Order By: Relevance
“…Our study shows that the proportion of patients who frequently interacted with pharmacist was very low, and the main reason for interaction was drug dosage queries. Lack of time and private areas for counselling were contributed for lower frequency of interaction of patients with pharmacist . Our findings were consistent with study on patients’ opinion of pharmacists and their role in healthcare system in Pakistan; however, it reported that drug alternatives queries were the main reason for interaction.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study shows that the proportion of patients who frequently interacted with pharmacist was very low, and the main reason for interaction was drug dosage queries. Lack of time and private areas for counselling were contributed for lower frequency of interaction of patients with pharmacist . Our findings were consistent with study on patients’ opinion of pharmacists and their role in healthcare system in Pakistan; however, it reported that drug alternatives queries were the main reason for interaction.…”
Section: Discussionsupporting
confidence: 89%
“…Lack of time and private areas for counselling were contributed for lower frequency of interaction of patients with pharmacist. [39] Our findings were consistent with study on patients' opinion of pharmacists and their role in healthcare system in Pakistan; [30] however, it reported that drug alternatives queries were the main reason for interaction. Additionally, drug-related queries might be the indication that doctors are not being able to spend enough time with patients including explanation of dosage of medications, probably a consequence of low doctor-to-population ratio (1:1724) in Nepal.…”
Section: Discussionsupporting
confidence: 88%
“…Studies conducted nationally and internationally highlight the lack of confidence of pharmacists in delivering services directly to patients and the need for them to develop specific skills for the clinical practice [33][34][35][36]. Besides understanding the theoretical and philosophical foundation of the professional practice, these skills include knowledge about the pharmacotherapy for a number of different medical conditions [30].…”
Section: Discussionmentioning
confidence: 99%
“…A knowledge scale was prepared and the score varied from 0-21 points and was classified into 3 levels according to the Blooms' cut off point. Based on the total score, the students' knowledge was then graded as low (0-11), medium (12)(13)(14)(15) and high (16)(17)(18)(19)(20)(21).…”
Section: Assessment Of Knowledgementioning
confidence: 99%
“…Studies carried out elsewhere have demonstrated a number of influential factors for self-medication practice including the level of education, family influence, easy availability of medicines, mild illness, previous experience of treating similar illness, economic status, lack of availability of healthcare personnel and exposure to advertisements [13][14][15]. Despite the reported decline in malaria transmission, morbidity and mortality in Dar es salaam [16], fever is still a major complaint in many outpatients which points out to the importance of non-malaria febrile illnesses.…”
Section: Introductionmentioning
confidence: 99%